A necessary optimality condition in two-dimensional screening - Araújo, A.; Vieira, S.; Calagua, B. (Springer Science and Business Media Deutschland GmbH, 2022)
This paper studies adverse selection problems with a one-dimensional principal instrument and a two-dimensional agent type. We provide an optimality condition that characterizes the bunching of continuum types. The approach is based on a reparameterization of the type space in terms of the endogenous optimal allocation level curves. The condition obtained is related with the optimality of two pooling types in the one-dimensional screening without the single-crossing. We illustrate the method by analyzing one example from the literature as well as a new example far from the linear-quadratic case
Keywords: Two-dimensional screening; Bunching; Non single-crossing; Quasilinear equation; Characteristic curves; https://purl.org/pe-repo/ocde/ford#1.01.00